2022
DOI: 10.1017/s1368980022001987
|View full text |Cite
|
Sign up to set email alerts
|

The global disease burden attributable to a diet low in fibre in 204 countries and territories from 1990 to 2019

Abstract: Objective: The relationship of a diet low in fiber with mortality has not been evaluated. This study aims to assess the burden of non-communicable chronic diseases (NCDs) attributable to a diet low in fiber globally from 1990 to 2019. Design: All data were from the Global Burden of Disease (GBD) Study 2019, in which the mortality, disability-adjusted life-years (DALYs), and years lived with disability (YLDs) were estimated with Bayesian geospatial regression using data at global, regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Appropriate dietary choices should be viewed as a part of a continuum of healthy lifestyle choices 28 . Except for a few countries or territories, the burden of disease attributable to low-fiber diets has been declining globally, but changes within the study period and estimates of effects are less clear 29 , 30 . Joinpoint regression and age-period-cohort analysis, which look at trends in burden indicators within the study period and estimate age-period and cohort effects, have significant advantages for assessing disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate dietary choices should be viewed as a part of a continuum of healthy lifestyle choices 28 . Except for a few countries or territories, the burden of disease attributable to low-fiber diets has been declining globally, but changes within the study period and estimates of effects are less clear 29 , 30 . Joinpoint regression and age-period-cohort analysis, which look at trends in burden indicators within the study period and estimate age-period and cohort effects, have significant advantages for assessing disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…While diets rich in whole grains, fruit, and legumes have been linked with dementia risk in some studies, the burden of non‐communicable chronic disease due to low dietary fiber in SSA has increased substantially between 1990 and 2019. 45 A study in the Central African Republic showed that reduced consumption of oleaginous foods was associated with a 3.7‐ and 2.8‐fold higher risk of mild cognitive impairment (MCI) and dementia, respectively. 46 The rising consumption of ultra‐processed foods, which is associated with cognitive decline, is a concerning trend in LMICs.…”
Section: Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…These foods are predominantly high in saturated fat, sodium, and added sugars, nutrients labelled to be of concern and recommended to limit across dietary guidelines globally ( 13 ). The diets also fail to meet food group recommendations and are consequently inadequate in meeting several macro- and micronutrient recommendations ( 13 , 15 ); in Australia and/or New Zealand, common nutrient inadequacies include calcium, vitamin D, iron, selenium, zinc, folate, thiamin, and vitamin B12 ( 16–18 ). Other factors impacting suboptimal dietary choices include (but are not limited to) affordability and sustainability, with refined ingredients often cheaper than their whole-food counterparts ( 19 ), and an increasing movement towards plant-based diets, containing, for example, processed meat and dairy alternatives ( 20 ).…”
Section: Introductionmentioning
confidence: 99%